RELATIONSHIP BETWEEN NITRIC OXIDE, ENZYMATIC ANTIOXIDANT SYSTEM AND ABA IN MAIZE UNDER LONG-TERM DROUGHT - MAGALHAES, PAULO CESAR; LAVINSKY, ALYNE OLIVEIRA; MELO, HEVERTON FERNANDO; ALVES, JUNIA CLARISSA; SOUZA, THIAGO CORRÊA; BARBOSA, ALICE PITA; RIBEIRO, CLEBERSON (REVISTA BRASILEIRA DE MILHO E SORGO, 2016)
The relationship between nitric oxide (NO) and up-regulation of the antioxidant system ABA-mediated in maize was evaluated under long-term drought. Two maize genotypes with contrasting drought tolerance (BRS1010 – sensitive and DKB390 - tolerant) were exposed to two soil water levels, field capacity (FC) and water deficit (WD) at pre-flowering. After 12 days under these conditions, plants were irrigated and soil water level kept at FC until harvest. The plants BRS1010 under water deficit (WD) showed lower catalase activity and reduced levels of NO, whereas ABA and malondialdehyde (MDA) levels increased compared to plants under FC. Although, DKB390 plants under WD did not present changes on the activity of enzymatic antioxidant system and ABA compared to plants at FC, and cellular damage remain unaltered; this fact was associated with the increase in NO levels. As a result, DKB390 plants under WD showed harvest index values 50% higher than BRS1010 under the same condition.